Correlation of online shopping deception awareness and susceptibility consequences on customers' online shopping behavior - Alfante, Dorothy Faye Español; Bayano, Samantha Jane Lumbaca; Servano, Aizel Salvy Lacsarom
This study used an explanatory research design to analyze the correlation between awareness on and susceptibility to online shopping deceptions, and online shopping behavior. Consumers' awareness on online shopping deceptions and their susceptibility to online shopping deceptions are the two factors that were given focus in this study in relation to online shopping behavior. Research hypotheses were formulated relating to the relationship between these variables. With the use of convenience non-probability sampling, a total of two hundred and six (206) respondents from Eastern Visayas were gathered and data were collected through an online survey. The research instrument used a five-point Likert scale and employed descriptive statistics, frequency distribution, and Spearman's Rho correlation for the statistical treatment. research results suggest that there was a significant moderately strong positive correlation between awareness and susceptibility. Similar results appeared for the correlation between awareness and susceptibility to online shopping deception, and online shopping behavior. Future research is needed to determine other variables that could further analyze online shopping behavior. Also, as this study used a nonparametric statistical test, proponents of the study suggest to future researchers to employ a parametric analysis to further confirm or negate the results of this study.